2018
DOI: 10.1097/jom.0000000000001251
|View full text |Cite
|
Sign up to set email alerts
|

Responsibilities of the Occupational and Environmental Medicine Provider in the Treatment and Prevention of Climate Change-Related Health Problems

Abstract: : Workers are uniquely susceptible to the health hazards imposed by environmental changes. Occupational and environmental medicine (OEM) providers are at the forefront of emerging health issues pertaining to working populations including climate change, and must be prepared to recognize, respond to, and mitigate climate change-related health effects in workers. This guidance document from the American College of Occupational and Environmental Medicine focuses on North American workers health effects that may o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…With increasing ambient temperatures due to climate change, the OEM provider can play a pivotal role in recommending heat warning systems, hydration interventions, and medical surveillance programs, using these newly elucidated biomarkers of injury, to limit the burden of disease. 64…”
Section: Discussionmentioning
confidence: 99%
“…With increasing ambient temperatures due to climate change, the OEM provider can play a pivotal role in recommending heat warning systems, hydration interventions, and medical surveillance programs, using these newly elucidated biomarkers of injury, to limit the burden of disease. 64…”
Section: Discussionmentioning
confidence: 99%
“…They did not even have the "methods" section along the text body, making it impossible to categorize them. All they had in common was the theoretical discussion about the impacts of climate change on occupational health and safety [22,26,[167][168][169][170][171][172][173][174][175][176][177][178][179].…”
Section: Discussion Categorymentioning
confidence: 99%
“…Further research is needed to understand how best to support employees affected by climate change. It has been suggested that occupational health providers need to have the ability to recognize and mitigate climate change-related health effects, including mental health effects [ 24 ] but further research on this topic is needed to provide appropriate guidance for providers.…”
Section: Discussionmentioning
confidence: 99%